Peripheral neuroblastic tumor of the kidney: case report and review of literature. Issue 6 (December 2018) - Moscheo, Carla; Campari, Alessandro; Podda, Marta Giorgia; Riccipetitoni, Giovanna; Collini, Paola; Renne, Salvatore Lorenzo; Vella, Claudio; Napolitano, Marcello; Luksch, Roberto
Introduction: Peripheral neuroblastic tumors (PNTs) account for 8%–10% of all pediatric tumors. Adrenal glands and sympathetic ganglia are the commonest site of tumor growth. In the clinicopathologic spectrum of PNTs, neuroblastoma and ganglioneuroma are the most primitive and the most mature tumor form, while ganglioneuroblastoma represents an intermediate state of maturation. Surgical resection is the therapy of choice in localized disease, but can lead to serious complications when performed in the presence of certain imaging-defined risk factors. Case presentation: We present a rare case of primary intrarenal ganglioneuroblastoma diagnosed in a teenager who underwent conservative surgery and, despite this, developed upper pole renal ischemia without loss of parenchymal function. Conclusion: We underline the complex management of these extremely rare cases of neuroblastic tumors, which require a dedicated multidisciplinary team.